The Effect of The Diorama Media-Assisted Core Type Operative Learning Model on Student Learning Outcomes - Julita Wati; Daska Aziz; Zalmita Novia (Journal Learning Geography, 2023)
This study aims to determine the effect of the CORE type cooperative learning model assisted by diorama media on learning outcomes in hydrofer material at SMA Negri 5 Banda Aceh. This type of research is Quasi Experimental Design. The population of this study were all students of class X IS SMA Negeri 5 Banda Aceh. Sampling was done by purposive sampling technique, taken from class X IS 3 (experimental class) of 29 students and class X IS 2 (control class) of 29 students. Data collection techniques by giving tests to students, namely pre-test and post-test. Data processing techniques using the t test. The results of data processing obtained tcount = 5.12 and ttable = 1.67. According to the test criteria, Ha is accepted if tcount ttable at a significance level of 5% and dk = (n1 + n2 – 2). Based on the calculation results obtained tcount ttable or 5.12 1.67 it can be stated that Ha is accepted, so it can be concluded that there is an influence of the CORE type cooperative learning model assisted by diorama media on learning outcomes in SMA Negeri 5 Banda Aceh. DOI: 10.23960/jlg.v4.i2.28606